2013
DOI: 10.3109/03014460.2013.852244
|View full text |Cite
|
Sign up to set email alerts
|

Colombia’s racial crucible: Y chromosome evidence from six admixed communities in the Department of Bolivar

Abstract: Heterogeneous patterns of admixture reveal a genetic substructure within the Department of Bolivar. On the paternal side, five out of the six communities studied exhibit a predominantly European gene pool. The exception is Palenque, where European input (38%) is more significant than we had expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 28 publications
1
26
0
6
Order By: Relevance
“…Since the 1980s, genetic and clinical studies of molecular HLA antigens (Bernal et al 1995), as well as of mtDNA and Y chromosomes (Keyeux et al 2002, Melton et al 2007, Rondón et al 2008, Noguera 2012, Noguera et al 2014, have shed fresh light on the genetic structures of Colombian populations, revealing a high degree of admixture between populations of different origins and a clear vision of antigenic diversity (Briceño et al 1996). Some results from the analysis of nucleotide diversity amongst these groups suggest past population bottlenecks, followed by later recovery (Mitchell et al 2000).…”
Section: Indigenous Populations Of Contemporary and Prehistoric Colombiamentioning
confidence: 99%
“…Since the 1980s, genetic and clinical studies of molecular HLA antigens (Bernal et al 1995), as well as of mtDNA and Y chromosomes (Keyeux et al 2002, Melton et al 2007, Rondón et al 2008, Noguera 2012, Noguera et al 2014, have shed fresh light on the genetic structures of Colombian populations, revealing a high degree of admixture between populations of different origins and a clear vision of antigenic diversity (Briceño et al 1996). Some results from the analysis of nucleotide diversity amongst these groups suggest past population bottlenecks, followed by later recovery (Mitchell et al 2000).…”
Section: Indigenous Populations Of Contemporary and Prehistoric Colombiamentioning
confidence: 99%
“…In studies of the populations of Cape Verde Islands [20,21] and Sao Tome Island [22,23], sex-specific genetic systems were used to elucidate both maternal and paternal origins. In the case of the Palenque, analysis of HLA autosomal markers and antigens [24,25], and recently NRY variation [26] has suggested a greater proportion of recent African descent (RAD) than other Colombian groups.…”
Section: Introductionmentioning
confidence: 99%
“…The European component represents about half of the gene pool of the population (49.1%), while 21.5% is from African contribution and 29.4% is Native American. It is very important to note that the proportion of Native American ancestry was higher than the previously reported [2,[3][4][5]. The cause of these findings may be, among others, the different set of AIMs used, the reference samples considered for the ancestry estimates, and the sample size.…”
Section: Resultsmentioning
confidence: 77%
“…Previous studies, focusing in uniparental markers and autosomal AIMs, had demonstrated that this population have more European and African ancestry than Native American [2,[3][4][5].…”
Section: Introductionmentioning
confidence: 91%